2010
DOI: 10.1007/s11540-010-9163-0
|View full text |Cite
|
Sign up to set email alerts
|

Improving Potato Tuber Quality and Production by Targeted Calcium Nutrition: the Discovery of Tuber Roots Leading to a New Concept in Potato Nutrition

Abstract: Calcium plays a major role in plant growth and development and in the maintenance and modulation of various cell functions, especially related to membrane structure and function and to cell wall structure. Calcium stabilizes cell membranes by bridging polar head groups of phospholipids at the membrane surface. Calcium is also an integral part of the cell wall where it provides stable intra-molecular linkages between pectin molecules, resulting in cell wall rigidity. A change in the cytosolic calcium concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…This suggests that sCAX1 transgenic lines may be affected by a decrease in apoplastic Ca 2+ . It is also interesting to note that hollow heart in potato is known to be caused by an abrupt increase in growth of the tuber tissue after a dry period (Palta, 2010). Our experiments measured cell wall biomass in tubers and found that there was ?1 g less dry weight of cell walls per 100 g of fresh tuber tissue in Atlantic and Russet Norkotah sCAX1 transgenic lines than in the control (Fig.…”
Section: Cell Wall Content In Tubers Decreases As a Consequence Of Ovmentioning
confidence: 65%
“…This suggests that sCAX1 transgenic lines may be affected by a decrease in apoplastic Ca 2+ . It is also interesting to note that hollow heart in potato is known to be caused by an abrupt increase in growth of the tuber tissue after a dry period (Palta, 2010). Our experiments measured cell wall biomass in tubers and found that there was ?1 g less dry weight of cell walls per 100 g of fresh tuber tissue in Atlantic and Russet Norkotah sCAX1 transgenic lines than in the control (Fig.…”
Section: Cell Wall Content In Tubers Decreases As a Consequence Of Ovmentioning
confidence: 65%
“…Placement of calcium is important for enhancing calcium uptake by the tuber as the main root does not supply the tuber with calcium (Palta, 2010). Addition of calcium to the tuber and stolon areas can result in a threefold increase in calcium concentration in the tuber peel and medullary tissue (Kratzke and Palta 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore to effectively increase tuber calcium supplemental calcium should be added during the tuber bulking stage because the tubers develop later in the season. Tubers have their own roots which take up water and calcium (Palta, 2010) and applications must be within reach of these tuber roots. An effective way of applying calcium is through fertigation (Westermann, 1993;Palta, 1996) while less soluble fertilizers can be applied by side dressing before the last hilling (Ozgen et al, 2006).…”
Section: Factors Affecting Calcium Uptakementioning
confidence: 99%
“…Increasing calcium concentration in the potato tubers helps reduce the incidence of tuber soft rot during storage, thereby increasing shelf life (Kratze and Palta, 1986;Palta, 2010). reported a correlation between tuber cell wall, calcium content and the level of resistance to soft rot while McGuire and Kelman (1983) found tuber calcium concentration to be high in the cortex and periderm.…”
Section: Effect Of Calcium On Plant Resistance To Soft Rotmentioning
confidence: 99%